2023
DOI: 10.3390/nu15081852
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Spermidine Supplementation Does Not Increase Spermidine Levels in Blood Plasma and Saliva of Healthy Adults: A Randomized Placebo-Controlled Pharmacokinetic and Metabolomic Study

Abstract: (1) Background: Spermidine is a biogenic polyamine that plays a crucial role in mammalian metabolism. As spermidine levels decline with age, spermidine supplementation is suggested to prevent or delay age-related diseases. However, valid pharmacokinetic data regarding spermidine remains lacking. Therefore, for the first time, the present study investigated the pharmacokinetics of oral spermidine supplementation. (2) Methods: This study was designed as a randomized, placebo-controlled, triple-blinded, two-armed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…However, since eukaryotes can already produce Spm, it means they can tolerate a certain level of Spm, as opposed to other antibiotics. Moreover, the introduction of Spm as a food supplement to treat or prevent other disease conditions, further supports the ability of eukaryotes to tolerate an appreciable level of Spm (Senekowitsch et al, 2023). Lastly, because Spm can reduce the MIC of known TB drugs and vice versa (Sao Emani and Reiling, 2023), a high dose may not be required after all, if used in combination with these antibiotics.…”
Section: Discussionmentioning
confidence: 91%
“…However, since eukaryotes can already produce Spm, it means they can tolerate a certain level of Spm, as opposed to other antibiotics. Moreover, the introduction of Spm as a food supplement to treat or prevent other disease conditions, further supports the ability of eukaryotes to tolerate an appreciable level of Spm (Senekowitsch et al, 2023). Lastly, because Spm can reduce the MIC of known TB drugs and vice versa (Sao Emani and Reiling, 2023), a high dose may not be required after all, if used in combination with these antibiotics.…”
Section: Discussionmentioning
confidence: 91%
“…Spermidine and other related polyamines may therefore elicit genoprotective effects and alleviate immunosenescence by acting as antioxidants, promoting repair, and reducing ROS burden through increased autophagy. Spermidine supplementation in humans is tolerated at doses tested up to 15 mg/day, though we note that supplementation does not detectably change blood spermidine levels, despite eliciting its beneficial anti-ageing effects (Schwarz et al, 2018;Wirth et al, 2018;Senekowitsch et al, 2023). Current clinical trials investigating whether spermidine supplementation (e.g., NCT05421546, spermidine at 6 mg/day) improves vaccine responses in old people will be greatly informative in translating in vitro studies to population interventions.…”
Section: Spermidinementioning
confidence: 89%
“…Interestingly, the spermidine supplementation dose used in these trials could be considered low, taking into account that daily intake of spermidine has been estimated to be highly variable between subjects, ranging from 5 to 15mg , currently registered clinical trials are evaluating doses of 4 to 6 mg and that a recent pharmacokinetic study suggested that doses less than 15mg are unlikely to exert any short-term effects. (Senekowitsch et al, 2023). Furthermore, Schwarz 2022, which was methodologically well-designed and had longer follow-up times, used a remarkably low spermidine dose, raising the possibility that the lack of clinical effect may have been associated with the low dose.…”
Section: Discussionmentioning
confidence: 99%